Neuromodulatory Support for Breathing and Cardiovascular Action During Development - Harper, Ronald M.; Kesavan, Kalpashri (Frontiers in Pediatrics, 2021)
Neonatal survival requires precise control of breathing and cardiovascular action, with fatal consequences or severe injury without support. Prematurity presents multiple opportunities to disrupt cardiorespiratory regulation, leading to expressions of apnea of prematurity, periodic breathing, and inappropriate cardiovascular responses to apnea. Failed breathing control can result from altered breathing drives, typically arising from untimely development of sensory or motor coordination processes. Some drives, such as temperature, are a special concern in neonates with low body mass, enhancing susceptibility to rapid body cooling. Chemical drives, such as pH or CO2 or O2, may be inadequately developed; in some conditions, such as congenital central hypoventilation syndrome (CCHS), breathing responses to CO2 or low O2 may be reduced or absent, and coupling of cardiovascular responses to breathing changes are abolished. Sleep states exert profound influences on both chemical and temperature drives, with rapid eye movement (REM) sleep reducing descending temperature influences, and state transitions significantly altering respiratory responses to chemical stimuli. In addition, neonates spend the majority of time in REM sleep, a state which induces a generalized inhibition of skeletal muscle activity that abolishes muscle tone to upper airway and thoracic wall muscles, enhancing the potential for obstructive sleep apnea. Although disrupted regulatory drives can often be replaced by positive (or negative) pressure ventilation, such as continuous positive airway pressure or mechanical ventilation, or enhanced by manipulating neurotransmitter action via caffeine, those approaches can exert negative consequences in the long term; the lungs of neonates, especially premature infants, are fragile, and easily injured by positive pressure. The consequences of caffeine use, acting directly on neural receptors, although seemingly innocuous in the near-term, may have long-term concerns and disrupts the integrity of sleep. The developmental breathing field needs improved means to support ventilation when one or more drives to respiration fail, and when the cardiovascular system, depending heavily on interactions with breathing, is compromised. Neuromodulatory procedures which use long-established reflexive mechanisms coupling limb movement with breathing can provide support for central and obstructive apnea, as well as for periodic breathing and cardiovascular action, particularly during sleep.